2023
DOI: 10.3389/fphys.2023.1173808
|View full text |Cite
|
Sign up to set email alerts
|

The mushroom body development and learning ability of adult honeybees are influenced by cold exposure during their early pupal stage

Abstract: The honeybees are the most important pollinator in the production of crops and fresh produce. Temperature affects the survival of honeybees, and determines the quality of their development, which is of great significance for beekeeping production. Yet, little was known about how does low temperature stress during development stage cause bee death and any sub-lethal effect on subsequent. Early pupal stage is the most sensitive stage to low temperature in pupal stage. In this study, early pupal broods were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…35℃ is considered the optimal temperature for honeybee development, and our previous studies have shown through tissue sections that brain development of new pupae stagnates after exposure to cold stress, and learning and memory are impaired in adults [20]. However, the physiological processes and molecular mechanisms behind this phenomenon of cold-stress effect have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35℃ is considered the optimal temperature for honeybee development, and our previous studies have shown through tissue sections that brain development of new pupae stagnates after exposure to cold stress, and learning and memory are impaired in adults [20]. However, the physiological processes and molecular mechanisms behind this phenomenon of cold-stress effect have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Deviation from the optimal temperature during development can result in abnormal development of honeybee broods, including abnormal external morphology of adult honeybee (proboscis, forewing, and hind leg) [17], and a shortened lifespan [18,19]. Due to the various evidence available, it is clear that cold stress can hinder the development of honeybee brains [20]. This includes a decline in the number of mushroom body synaptic complexes [21], leading to impaired learning, memory, and foraging abilities in adult honeybees after they emerge [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the neural circuit level, it has been established that the brain region responsible for learning and memory formation in insects is the mushroom body (MB) [6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. A complete connectome of the larval brain [32] as well as the specific neural circuit responsible for olfactory memory [33] have been recently mapped.…”
Section: Larval Learning and Memorymentioning
confidence: 99%